An Eighteenth Century Record of the Evils of Depreciation - Mixter, C. W. (Quarterly Journal of Economics, 1896)
An Eighteenth Century Record of the Evils of Depreciation Get access C. W. Mixter C. W. Mixter Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 10, Issue 2, January 1896, Pages 240–243, https://doi.org/10.2307/1882383 Published: 01 January 1896